Aplikasi Desain Sampling pada Statistika dalam Stratifikasi Ekonomi Masyarakat Urban - Nufus, Alifa Baiduri Hayatun (Future Science, 2024)
Social stratification means grouping a society into certain classes. Where this grouping shows the differences in status that exist with-in a general group of society. Every society has something it values, such as; money, land, and objects of economic value, it is also possi-ble that they are in the form of power, knowledge, piety in religion, or descent from a certain family, occupation and the like. This re-search takes the theme of Economic Stratification in urban society using Sampling Design in Statistics, and then analyzes the relation-ship and causality of Stratification in urban society. The method used is descriptive qualitative. The data source used is a secondary data source and uses a type of library research (Library Research). The research results show that those with low socioeconomic sta-tus tend to have high social relationships, while those with high so-cioeconomic status tend to have relatively low relationships. In other words, what influences patterns of social interaction or social relations in urban communities is socio-economic status, type of work, income level and education level. Apart from that, there are other factors that determine patterns of social interaction or social relations in the city.